FOUNDATIONS OF INTELLIGENT AGENT DESIGN: FROM ARCHITECTURE TO MATHEMATICAL MODELING - КrykhiskyiM. V.; VavrykТ. O.; Hobyr, L. M. (Systems and Technologies, 2025)
Intelligent agents (IA) have become a central topic of modern research in the field of artificial intelligence. They are an important component of modern information technologies used to automate complex tasks such as data processing, decision-making, and adaptive learning. The development of intelligent agents is a complex, multifaceted process that includes the choice of architecture, the development of decision-making algorithms, and integration with the environment. Over the past decades, many new technologies and approaches have emerged that can significantly improve the effectiveness of agents in real-world applications. The article explores the conceptual foundations of intelligent agents, various approaches to their design, and key technologies that allow for the creation of autonomous and adaptive systems. The authors consider the general algorithm of the functioning of an intelligent agent, its main stages and architecture. An overview of the concept of intelligent agents is presented, including their basic properties, models of interaction with the environment and adaptive mechanisms. The main attention is paid to a universal algorithm that can be adapted to various applications in the field of artificial intelligence (AI). The article presents a mathematical basis for describing intelligent agents, which allows modeling their behavior, decision-making and interaction with the environment. The article presents a mathematical basis for describing intelligent agents, which allows modeling their behavior, decision-making and interaction with the environment. The main components of agents, their formalization through theoretical models and corresponding algorithms are considered. The mathematical description of agents is also considered, taking into account their properties, such as adaptability, autonomy and interaction with the environment. Mathematical analysis of intelligent agents is an important and rapidly developing area, covering a wide range of methods and techniques for modeling, analyzing and optimizing the behavior of intelligent agents.